Putting the discourse to work: On outlining a praxis of democratic leadership development. Issue 4 (September 2016) - Smolović Jones, Sanela; Smolović Jones, Owain; Winchester, Nik; Grint, Keith
This article offers a praxis of democratic leadership development, arguing that the framework presented can act as a means of rethinking how collective forms of leadership are developed within and between organisations. Building on notions of leadership development as process and person-based, we interpret these as contested, democratic and contingent discursive achievements in a process of developing. Post-foundationalist theory, particularly the work of Ernesto Laclau, is introduced as a means of 'democratizing' key dimensions of leadership development: working with 'leadership' and 'democracy' as empty-floating signifiers holding the potential to generate energetic engagements between leadership development participants. A framework consisting of four dimensions is introduced, with particular attention paid within each dimension to its practice relevance. First, we seek to democratise the leader-subject, reinterpreted as a contested and contingent signifying subject of discourse. Second, we seek to radicalise the process of development through foregrounding conflict and agonistic practice. Third, we introduce the notion of symbolic violence as a means of thinking about direction setting within development contexts. Fourth, we argue for development that pays attention to the unknown, to the gaps in discourse. We explore each dimension in relation to an illustrative example, a cross-organisational women's group in the Pacific.